5+3(2x-4)=3+2x

Simple and best practice solution for 5+3(2x-4)=3+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+3(2x-4)=3+2x equation:


Simplifying
5 + 3(2x + -4) = 3 + 2x

Reorder the terms:
5 + 3(-4 + 2x) = 3 + 2x
5 + (-4 * 3 + 2x * 3) = 3 + 2x
5 + (-12 + 6x) = 3 + 2x

Combine like terms: 5 + -12 = -7
-7 + 6x = 3 + 2x

Solving
-7 + 6x = 3 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-7 + 6x + -2x = 3 + 2x + -2x

Combine like terms: 6x + -2x = 4x
-7 + 4x = 3 + 2x + -2x

Combine like terms: 2x + -2x = 0
-7 + 4x = 3 + 0
-7 + 4x = 3

Add '7' to each side of the equation.
-7 + 7 + 4x = 3 + 7

Combine like terms: -7 + 7 = 0
0 + 4x = 3 + 7
4x = 3 + 7

Combine like terms: 3 + 7 = 10
4x = 10

Divide each side by '4'.
x = 2.5

Simplifying
x = 2.5

See similar equations:

| 3y+7y=22 | | g^2+3g=238 | | 3y-5x-12=0 | | 2/15=3/2(4/9x-4) | | (1/3)9×3 | | 1/3y-2=1/10y | | P^2-16pq-36q^2=0 | | 48x^2-27=0 | | 3x^2+9x+7= | | 5x+29y=-13 | | 9x^2+2x+2= | | 7x^2+3x+9= | | X^4-4x^2=21 | | X^5+7x^2=-12x | | 5(6x+1)=-25 | | g(x)=[x+2]-4 | | 2/3×1/2 | | -7n(5n-4)=0 | | 2(5+4x)=34 | | gv-q=6h | | gj-r=4c | | 3x^3+12x-2=0 | | Y=2x^2+6x-10 | | 5.00+0.80=14.60 | | 14=24-5p | | 0.25=x/300 | | (6x^2+4y-2)-(4x^2+y-5)=C | | 5x+8=-8x+5 | | 1/3(4 | | 2-6c=-16 | | 4x^3+24x=-1 | | -4=x/10-5 |

Equations solver categories